Lioness rampant - Pierce, Tamora (Pierce, Tamora. Song of the lioness, 1997)
Alanna continues to create her own life as a female warrior when she and new companions journey to the Roof of the World seeking the powerful Dominion Jewel, perhaps the last hope of saving her country from dissension and hostile magic.